Analysis of EGFR mutation frequency and coexistence of KRAS and EGFR mutations using RT-PCR in lung adenocarcinoma: may a clinical and pathological model of a patient’s qualification for targeted therapy have an impact on time to obtain genetic results? - Lewandowska, Marzena Anna; Jóźwicki, Wojciech; Starzyński, Jarosław; Kowalewski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
In Poland, lung cancer is the most common cause of cancer deaths among men, and since 2009 in women as well. Non-small cell lung carcinoma (NSCLC) can lead to abnormalities in the metabolism of EGFR, such as strong EGFR protein expression, amplification or presence of somatic mutations in the tyrosine kinase domain (TK). Targeted therapy (EGFR TK inhibitors) for patients diagnosed with activating EGFR mutations is more effective than standard chemotherapy, but the key to success is proper classification of the patient, carried out through the cooperation of an interdisciplinary team: thoracic surgeons, pathologists, geneticists/molecular biologists and oncologists. Eligibility for the study included clinical and pathological assessment. Genetic testing was performed using real-time PCR: we analysed 29 most common EGFR mutations (Entrogen) and 9 most common KRAS mutations (TibMolBiol). Activating mutations were identified in 10 of the 77 patients (13%) in exons 18,19, 20 or 21, but the vast majority in exons 19 and 21. In patients with EGFR mutation we detected wild-type KRAS, which suggests distinct tumor biology. Average waiting time for genetic results on DNA isolated from surgery material and cytology was 9 days. Molecular assessment of tumor tissue allows for adjustment of chemotherapy to the tumor biology, which is consistent with the intention of personalized medicine. Good cooperation between the surgeon, pathologist and genetic diagnostician makes it possible to shorten the optimal waiting time for targeted therapy.